Pengaruh konsentrasi Chemical Cleaning Agen (HCI Dan Detergen) Serta Tekanan Trans-Membran Dalam Meregenerasi Kinerja Membran Ultrafiltrasi Pada Penyaringan air Gambut (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The main challenge in the use of membrane technology is fouling. This research aims to study the trans-membrane pressure on the flux, studied the effectiveness and efficiency of HCl as chemical cleaning agent and detergents in the regeneration of ultrafiltration membranes in water filtration surgery peat. The study was conducted using ultrafiltration membranes with water bait peat. The method used is by varying the operating pressure of 1 bar and 1.5 bar, variations in the concentration of HCl and detergents 1%, 1.5% and 2%. Peat water filtration process lasted 120 minutes and wash each time is 30 minutes, the highest level of effectiveness of washing detergent obtained 20.77% using 2% and trans-membrane pressure of 1 bar, the highest leaching efficiency based on the value of the flux recovery 82.89 % and based on the resistance value of 22.73% removal. Value highest average flux after chemical leaching obtained 0.48 ml / menit.cm2 using detergent.Keywords: peat water, chemical cleaning agent, fouling, ultrafiltration membranes.